PENGARUH STRUKTUR MODAL DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN NON-KEUANGAN DI INDONESIA - Anastasya, Stella Lewinsky; Tjhai, Fung Jin (E-Jurnal Akuntansi TSM, 2024)
This study aims to analyze how the capital structure, institutional ownership, managerial ownership, profitability, company size, dividend policy, and current ratio influence the firm value. The research used all companies listed on the Indonesia Stock Exchange (IDX) except for the financial sector over a 3-year period, from 2020 to 2022. Purposive sampling was employed as the sampling method, and multiple regression analysis was used for data analysis. There were 65 companies and 195 data that met the research criteria. The research findings indicate that capital structure and profitability have a positive influence on company value. High capital structure and profitability lead investors to perceive that the company has promising prospects in the future thereby increasing firm value. Company size has a negative impact on company value because having substantial but idle assets can adversely affect company performance which results decreasing firm value. However, institutional ownership, managerial ownership, dividend policy, and current ratio do not affect firm value.